Measuring the seeds of ion outflow: Auroral sounding rocket observations of low‐altitude ion heating and circulation. Issue 2 (8th February 2016) - Fernandes, P. A.; Lynch, K. A.; Zettergren, M.; Hampton, D. L.; Bekkeng, T. A.; Cohen, I. J.; Conde, M.; Fisher, L. E.; Horak, P.; Lessard, M. R.; Miceli, R. J.; Michell, R. G.; et al.
Abstract: We present an analysis of in situ measurements from the MICA (Magnetosphere‐Ionosphere Coupling in the Alfvén Resonator) nightside auroral sounding rocket with comparisons to a multifluid ionospheric model. MICA made observations at altitudes below 325 km of the thermal ion kinetic particle distributions that are the origins of ion outflow. Late flight, in the vicinity of an auroral arc, we observe frictional processes controlling the ion temperature. Upflow of these cold ions is attributed to either the ambipolar field resulting from the heated electrons or possibly to ion‐neutral collisions. We measure E → × B → convection away from the arc (poleward) and downflows of hundreds of m s −1 poleward of this arc, indicating small‐scale low‐altitude plasma circulation. In the early flight we observe DC electromagnetic Poynting flux and associated ELF wave activity influencing the thermal ion temperature in regions of Alfvénic aurora. We observe enhanced, anisotropic ion temperatures which we conjecture are caused by transverse heating by wave‐particle interactions (WPI) even at these low altitudes. Throughout this region we observe several hundred m s −1 upflow of the bulk thermal ions colocated with WPI; however, the mirror force is negligible at these low energies; thus, the upflow is attributed to ambipolar fields (or possibly neutral upwelling drivers). The low‐altitude MICA observations serve to inform future ionospheric modeling and simulations of (a) the need to consider the effects of heating by WPI at altitudes lower than previously considered viable and (b) the occurrence of structured and localized upflows/downflows below where higher‐altitude heating rocesses are expected. Key Points: In situ observations of low‐altitude fine‐scale structure and plasma circulation Wave‐particle interactions heat ionosphere at altitudes below 325 km In situ observations of upflows in an auroral arc with downflows poleward of arc